The New Era of Long-Range “Zero-Interception” Ambient Backscattering Systems: 130 m with 130 nA Front-End Consumption - Daskalakis, Spyridon Nektarios; Georgiadis, Apostolos; Tentzeris, Manos M.; Goussetis, George; Deligeorgis, George (Sensors (Basel, Switzerland), 2022)
Internet of Things applications based on backscatter radio principles have appeared to address the limitations of high cost and high power consumption. While radio-frequency identification (RFID) sensor nodes are among the most commonly utilized state-of-the-art technologies, their range for passive implementations is typically short and well below 10 m being impractical for “rugged” applications where approaching the tag at such proximity, is not convenient or safe. In this work, we propose a long-range “zero interception” ambient backscatter (LoRAB) communication system relying on low power sensor (tag) deployments. Without employing a dedicated radio transmission, our technology enables the “zero interception” communication of the tags with portable receivers over hundreds of meters. This enables low-cost and low-power communications across a wide range of missions by using chirp spread spectrum (CSS) modulation on ambient FM signals. A laboratory prototype exploiting commercial components (laptops, DAQ, software-defined radios (SDR) platform) have demonstrated the potential by achieving 130 m tag-to-reader distance for a low bit rate of 88 bps with the modulator current consumption at around 103 nA.